Effect of Text-to-speech Software on Academic Achievement of Students with Dyslexia - Bhola, Neeti (Integrated Journal for Research in Arts and Humanities, 2022)
Dyslexia is a neurobiological disorder that creates serious difficulties in learning process. Being a special learning disorder, it demands special learning environment with a blend of right approach, method and technology. Text to speech software comes under the head of assistive technology that helps dyslexic children understand and assimilate structure sound and meaning of the words. Present study is an experimental study in which 20 students of 6-12 years of age range were selected and randomly distributed in experimental and control group. Experimental group was taught with text to speech software for four months while control group received no treatment and was taught by conventional method of teaching. In the beginning of the study a pretest was conducted in order to know the prevalent differences among the groups. After four months of intervention post test was conducted. Results revealed that students in experimental group performed significantly better than the control group. Text to speech software contributed to remarkable gains in the achievement of students with dyslexia.